Quatsomes Loaded with Squaraine Dye as an Effective Photosensitizer for Photodynamic Therapy - Nicolò Bordignon; Mariana Köber; Giorgia Chinigò; Carlotta Pontremoli; Ettore Sansone; Guillem Vargas-Nadal; Maria Jesus Moran Plata; Alessandra Fiorio Pla; Nadia Barbero; Judit Morla-Folch; Nora Ventosa (MDPI AG, 2023)
Photodynamic therapy is a non-invasive therapeutic strategy that combines external light with a photosensitizer (PS) to destroy abnormal cells. Despite the great progress in the development of new photosensitizers with improved efficacy, the PS's photosensitivity, high hydrophobicity, and tumor target avidity still represent the main challenges. Herein, newly synthesized brominated squaraine, exhibiting intense absorption in the red/near-infrared region, has been successfully incorporated into Quatsome (QS) nanovesicles at different loadings. The formulations under study have been characterized and interrogated in vitro for cytotoxicity, cellular uptake, and PDT efficiency in a breast cancer cell line. The nanoencapsulation of brominated squaraine into QS overcomes the non-water solubility limitation of the brominated squaraine without compromising its ability to generate ROS rapidly. In addition, PDT effectiveness is maximized due to the highly localized PS loadings in the QS. This strategy allows using a therapeutic squaraine concentration that is 100 times lower than the concentration of free squaraine usually employed in PDT. Taken together, our results reveal the benefits of the incorporation of brominated squaraine into QS to optimize their photoactive properties and support their applicability as photosensitizer agents for PDT.